Draft genome sequence of a CTX-M-15-producing Escherichia coli ST345 from commercial chicken meat in Brazil - Casella, Tiago [UNESP]; Cerdeira, Louise T.; Fernandes, Miriam R.; Souza, Tiago A.; Haenni, Marisa; Madec, Jean-Yves; Lincopan, Nilton; Nogueira, Mara C. L. (Elsevier B.V., 2017)
Escherichia coli, the main host of the CTX-M-15 extended-spectrum beta-lactamase (ESBL) enzyme, is widely distributed and exchanged between the environment, animals and humans. Therefore, identification of blaCTX-M-15-positive lineages in food has a significant impact on public health. In this regard, until the end of 1990s, ESBL-producing isolates were mainly associated with hospital-acquired infections, with a predominance of SHV-and TEM-type enzymes. In recent years, a new trend has been observed among ESBL-producers, where most isolates now harbour CTX-M-type, being further isolated from community-acquired infections. Nowadays, CTX-M-15 has been recognised as the most important ESBL variant, invading virtually all human and animal compartments, leading to a global pandemic. Thus, whilst the rapid emergence and dissemination of CTX-M-15 among E. coli isolates has generated a large genetic reservoir from which other members of the Enterobacteriaceae family can easily acquire this resistance gene, there are an increasing number of new reservoirs and transmission mechanisms that must be investigated. In this study, we present the draft genome sequence of a CTX-M-15-producing E. coli ST345 isolated from commercial chicken meat in Brazil. This draft genome can be used as a reference sequence for comparative analysis among CTX-M-15-producers. (C) 2017 Published by Elsevier Ltd on behalf of International Society for Chemotherapy of Infection and Cancer.
Keywords: Escherichia coli; Extended-spectrum beta-lactamase; IncX1; Food; WGS; Brazil